Safety of Cinnamon: An Umbrella Review of Meta-Analyses and Systematic Reviews of Randomized Clinical Trials - Gu, Dan-Tong; Tung, Tao-Hsin; Jiesisibieke, Zhu Liduzi; Chien, Ching-Wen; Liu, Wen-Yi (Frontiers in Pharmacology, 2022)
Purpose: Many evidence-based studies have indicated that cinnamon has therapeutic effects. However, it may not be entirely safe and its adverse effects may be ignored. The present umbrella review was conducted to elucidate the safety of cinnamon. Methods: Pertinent meta-analyses and systematic reviews of randomized controlled trials on cinnamon use in humans were identified by searching PubMed, EMBASE, and the Cochrane Library from their inception to September 15, 2021. All meta-analyses and systematic reviews on the safety or adverse effects of cinnamon were considered. PRISMA 2020 was used as the standard of reporting (PRISMA registration ID: 286746). Results: We identified three meta-analyses and one systematic review that described the safety of cinnamon. The quality of the meta-analysis and systematic reviews was evaluated using “Assessing the Methodological Quality of Systematic Reviews.” Their quality was rated as low in two (50%) instances and moderate in two (50%). There were no significant toxic- or side effects between cinnamon group and placebo group regardless of dose and duration. Conclusion: There is evidence to support that the use of cinnamon has no adverse reactions. It can improve the health status of patients as an adjuvant treatment. Future studies exploring better profile risks and protective factors for cinnamon use-related adverse effect are needed, in order that preventive approaches can be developed.